Textile Industry and Environment 2019
DOI: 10.5772/intechopen.85127
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Cotton Spinning Mill Wastes in Yarn Production

Abstract: Efficient use of natural resources and utilization of recoverable wastes are getting more and more important day by day since recovering wastes have both economic and environmental benefits. As the source material costs constitute the majority of the yarn production costs, decreasing raw material costs provide considerable advantages for spinners. From the point of textile manufacturing, various production wastes can be reused in textile industry. In each step, from ginning (for cotton fibers) to end product f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Considering ecological and economic aspects, companies are required to launch new technologies that can process various fibers with lower quality than virgin fiber sources or can adapt to different processed fibers and settings suitable for various fibers. 1 Textile waste has two main categories: production and post-production waste. 1,2 Production waste is formed during each production stage (from fiber to yarn, from yarn to fabric and cloth, or technical fabric processing).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering ecological and economic aspects, companies are required to launch new technologies that can process various fibers with lower quality than virgin fiber sources or can adapt to different processed fibers and settings suitable for various fibers. 1 Textile waste has two main categories: production and post-production waste. 1,2 Production waste is formed during each production stage (from fiber to yarn, from yarn to fabric and cloth, or technical fabric processing).…”
mentioning
confidence: 99%
“…1 Textile waste has two main categories: production and post-production waste. 1,2 Production waste is formed during each production stage (from fiber to yarn, from yarn to fabric and cloth, or technical fabric processing). Post-production waste is related to the use of end products.…”
mentioning
confidence: 99%
“…As the proportion of waste fibers increased, the air permeability of the fabrics decreased depending on the yarn hairiness. For pilling values, the highest results were obtained for fabrics with card waste with the highest short fiber content [28].…”
Section: Ute Et Al Produced Single Jersey Knitted Fabricsmentioning
confidence: 97%
“…Cotton fiber is still a famous textile material for clothing in tropical regions such as Indonesia. Along with the increasing demand of clothing textile from cotton, the cotton yarn spinning industry was still left out up to 11% of its raw material as wastes in the form of short cotton fibers [1]. Hence, some of them could not be recycled back to the spinning mills due to a down-graded fiber quality in term of fiber length, strength, micronaire, and uniformity.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, waste fibers generated in spinning mills can be returned to the same blend from which they came up. However, only up to 5% of wastes can be used in both carded ring-spun yarn and fine rotorspun yarn, 2.5% of wastes used for combed yarns, and about 10 and 20% of wastes used for medium and coarser rotor yarns, respectively [1]. A study of cotton fiber wastes recycling for both conventional ring-spun and open end-rotor yarn spinning found that blend yarns with pneumafil wastes resulted with better yarn qualities.…”
Section: Introductionmentioning
confidence: 99%